2013
DOI: 10.1111/tme.12037
|View full text |Cite
|
Sign up to set email alerts
|

RHD*weak partial 4.0 is associated with an altered RHCE*ce(48C, 105T, 733G, 744C, 1025T) allele in the Tunisian population

Abstract: The RHD*weak partial 4.0 allele syn. RHD*09.03 was estimated to occur 1 in 47 among D+ Tunisians. There was no evidence for other RHD alleles included in the weak D type 4 cluster.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…The weak D Type 4.0 was the most prevalent molecular weak D type in Tunisians, confirming our previously published data . Comparing our current data (Table ), we concluded that only approximately 69% of all Tunisian donors expressing the weak D Type 4.0 phenotype (53 of a calculated 77) were actually typed as having a serologic weak D phenotype.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…The weak D Type 4.0 was the most prevalent molecular weak D type in Tunisians, confirming our previously published data . Comparing our current data (Table ), we concluded that only approximately 69% of all Tunisian donors expressing the weak D Type 4.0 phenotype (53 of a calculated 77) were actually typed as having a serologic weak D phenotype.…”
Section: Resultssupporting
confidence: 90%
“…To a smaller extent, this caveat also applies to alleles of the weak D Type 4 cluster. For instance, the frequency of weak D Type 4.0 is actually 1:105, as determined by PCR in random donors …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations